An Empirical Model of Sectoral Movements by Unemployed Workers - Thomas, Jonathan M. (Journal of Labor Economics, 1996)
Using Canadian data, I investigate the relationships among sectoral mobility, unemployment spells, and total unemployment. Recent North American evidence suggests that incidence shifts toward high wage-high tenure workers may increase equilibrium unemployment through decreasing sectoral mobility and increasing spells. Using a multiple spell transition model, I find that, while shifts toward such workers may have these effects, composition changes that lead to higher mobility can also increase unemployment. A further investigation into the relative roles of mobility and spell lengths in driving total unemployment indicates that the influence of the former is comparatively small.